The Importance of the Strong Connection Between Native Language and History in Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides information on the specific features of problem-based learning technologies, their use in the learning process, and especially the advantages of using them in native language lessons.